AKULTURASI ESTETIK BUNGONG HIAS DALAM MASJID BAITURRAHMAN KOTA BANDA ACEH - M.zaki Al Syafani (Pascasarjana Institut Seni Indonesia Padang Panjang, 2021)
Research on the aesthetic acculturation of the ornamental Bungong Baiturrahman mosque uses the theoretical framework method as an analytical scalpel; acculturation theory leads to Koentjaraningrat's thoughts, aesthetic theory, and Charles Sanders Pierce's semiotic theory understand communication evidence of signs from a reality. The analysis of the aesthetic ornamental bungong on the cross between European and Middle Eastern cultures traces the process of acculturation that affects the Baiturrahman bungong decorative mosque based on the communication literature of icon, index, and symbol indicators. The shape and meaning of ornamental bungong are based on a semiotic representation of flora, nature, calligraphy and arabesque. The elements of flora consist of Bungong Meusingklet, Bungong Ban Keumang, Bungong Meulu and Pucok Rebong. The natural form consists of a bulen star, rante, puta taloe, si oen¸ cloud, and kande lamp. Calligraphy and arabesque forms consist of geometric elements and the pronunciation of Allah with the art form of calligraphy. The ornamental bungong has a philosophical meaning as local wisdom of cultural values in regulating the social life of the Acehnese people and also influences the reference to the shape of the ornamental bungong both in terms of architecture and the application of objects scattered throughout the archipelago.Keywords: Acculturation; Aesthetics; Ornamental BungongAbstrakPenelitian pada akulturasi estetik bungong hias masjid Baiturrahman menggunakan metode kerangka teori sebagai pisau bedah analisis, teori akulturasi mengarah pada pemikiran Koentjaraningrat, teori estetika dan teori semiotika Charles Sanders Pierce memahami komunikasi pembuktian tanda-tanda dari sebuah kenyataan. Analisis bungong hias estetik terhadap persilangan budaya Eropa dan Timur Tengah, menelusuri dengan proses perjalanan akulturasi yang mempengaruhi masjid Baiturrahman bungong hias berdasarkan literatur komunikasi indikator ikon, indeks, dan symbol. Bentuk dan pemaknaan bungong hias berdasarkan semiotik dari hasil representasi flora, alam, kaligrafi dan arabesque. Bentuk unsur flora terdiri bungong meusingklet, bungong ban keumang, bungong meulu dan pucok rebong. Bentuk alam terdiri dari bintang bulen, rante, puta taloe, awan si oen¸dan lampu kande. Bentuk kaligrafi dan arabesque terdiri dari unsur geometris dan lafad Allah dengan bentuk seni kaligrafi. Bungong hias tersebut memiliki makna filosofis sebagai kearifan lokal dari nilai-nilai budaya dalam mengatur kehidupan sosial masyarakat Aceh dan juga mempengaruhi acuan bentuk bungong hias baik dari segi arsitektur dan penererapan terhadap objek yang tersebar di Nusantara.Kata Kunci: Akulturasi, Estetik, Bungong Hias